Long‐gap esophageal atresia: traction‐growth and anastomosis – before and beyond. Issue 4 (16th May 2013) - Bagolan, P.; Valfrè, L.; Morini, F.; Conforti, A.
Summary Long‐gap esophageal atresia (LGEA) is still a major surgical challenge. Options for esophageal reconstruction include the use of native esophagus or esophageal replacement with stomach, colon, or small intestine. Nonetheless, there is a consensus among most pediatric surgeons that the preservation of the native esophagus is associated with better postoperative outcomes. Thus, every effort should be made to conserve the native esophagus. The present study is aimed at critically reporting our experience focused on a standardized protocol based on the preoperative assessment of the gap in all cases and reviewing the present literature because no consensus is available regarding many aspects of LGEA (from definition to treatment). All newborn infants treated since 1995 for esophageal atresia (EA), regardless of type, were included in the present study. Identification of LGEA patients (gap ≥3 vertebral bodies) was performed based on preoperative esophageal gap measurement. The selected patients were grouped based on EA type (A/B vs. C/D) and whether they were referred from an outside institution or not. Postoperative outcome was compared. Statistical analysis was performed with the Fisher's exact test and Mann–Whitney test as appropriate, with P < 0.05 considered statistically significant. Two hundred and nineteen patients have been consecutively treated between 1995 and 2012 with the following EA subtypes: type: A 25 (11.4%); B 6 (2.7%); C 182 (83.1%); D 3 (1.4%); E 3 (1.4%). Fifty‐seven patients (26%) were classified as LGEA: type A‐B, 31 (54.4%); type C‐D, 26 (45.6%). Twenty seven (47%) of these patients were referred after at least one failed attempt at esophageal correction: type A‐B, 15 (55%); type C‐D, 12 (45%). Only one patient ultimately required esophageal substitution, with an overall survival rate of 94%. A standardized perioperative protocol enhances the possibility of preserving the native esophagus in cases of LGEA. Gap measurement can be accurately defined before surgery in all patients with EA. Esophageal anastomosis (either immediate or delayed repair) is almost always feasible; esophageal substitution should only be considered after a rigorous attempt at achieving end‐to‐end esophageal anastomosis.